2021
DOI: 10.3390/genes12040555
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Neurobehavioral Responses to Caffeine Administration during Sleep Deprivation: A Randomized, Cross Over Study (NCT03859882)

Abstract: This study investigated whether four single nucleotide polymorphisms (SNPs) moderated caffeine effects on vigilance and performance in a double-blind and crossover total sleep deprivation (TSD) protocol in 37 subjects. In caffeine (2 × 2.5 mg/kg/24 h) or placebo-controlled condition, subjects performed a psychomotor vigilance test (PVT) and reported sleepiness every six hours (Karolinska sleepiness scale (KSS)) during TSD. EEG was also analyzed during the 09:15 PVT. Carriers of the TNF-α SNP A allele appear to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 62 publications
(75 reference statements)
3
32
4
Order By: Relevance
“…The T1083C polymorphism (SNP-ID: rs5751876) in the adenosine A2A receptor ( ADORA2A ) gene also contributes to an individual’s neurobehavioral vulnerability to sleep loss: a recent study found that T allele carriers had worse vigilant attention performance (greater number of PVT lapses) than C/C individuals after 32 h TSD [ 67 ]. Similarly, another study showed that C/T carriers exhibited greater PVT performance resilience during chronic SR compared with T/T carriers [ 68 ].…”
Section: Genetic Polymorphisms Related To Differential Neurobehavioral Vulnerability To Sleep Lossmentioning
confidence: 99%
See 4 more Smart Citations
“…The T1083C polymorphism (SNP-ID: rs5751876) in the adenosine A2A receptor ( ADORA2A ) gene also contributes to an individual’s neurobehavioral vulnerability to sleep loss: a recent study found that T allele carriers had worse vigilant attention performance (greater number of PVT lapses) than C/C individuals after 32 h TSD [ 67 ]. Similarly, another study showed that C/T carriers exhibited greater PVT performance resilience during chronic SR compared with T/T carriers [ 68 ].…”
Section: Genetic Polymorphisms Related To Differential Neurobehavioral Vulnerability To Sleep Lossmentioning
confidence: 99%
“…One study found that caffeinated coffee mitigated performance deficits on tasks of vigilant attention and executive control, but not self-rated sleepiness, induced by five consecutive nights of SR in C/C allele carriers [ 71 ]. Furthermore, caffeine counteracted 40 h TSD-induced decrements in PVT performance in non-HT4 allele carriers but was not effective in individuals with the HT4 haplotype [ 69 ], although another study showed that the ADORA2A genotype did not influence the mitigatory effect of caffeine on PVT performance during 38 h TSD [ 67 ]. In addition, although A 1 adenosine receptor (A 1 AR) availability has been linked to the mitigatory effects of recovery sleep on neurobehavioral performance following 52 h TSD, this effect was not moderated by the ADORA2A genotype [ 72 ].…”
Section: Genetic Polymorphisms Related To Differential Neurobehavioral Vulnerability To Sleep Lossmentioning
confidence: 99%
See 3 more Smart Citations